Rectal lymphogranuloma venereum: an emergent clinical presentation: Lymphogranuloma venereum (Actualizaciones en Sida e Infectología, 2021)
Rectal lymphogranuloma venereum: an emergent clinical presentationAbstractLymphogranuloma venereum is a rare sexually transmitted infection (STI) caused by serotypes L1, L2 and L3 of Chlamydia trachomatis.For over a decade, there has been a considerable increase in the incidence of LGV proctitis in almost exclusively men who have sex with men with STI risk behaviors.Four  cases of rectal LGV are reported.
Keywords: lymphogranuloma venereum, proctitis, Chlamydia trachomatis, sexually transmitted disease.